Termite Communities in Sugarcane Plantations in Southeastern Brazil: an Ecological Approach - Junqueira, Luciane Kern; Gonçalves, Edmilson Ricardo; Teixeira, Lucas Manuel Cabral (EntomoBrasilis, 2015)
Termites are key components of soil fauna, playing an essential role in organic matter decomposition and nutrient cycling. However, they can cause significant economic losses in commercial plantations, such as sugar cane. Therefore, the correct identification of termite species is critical for pest control. Here, we evaluated the species richness, abundance and functional groups of termites in sugarcane plantations in 53 cities throughout the state of São Paulo, southeastern Brazil. We also analyzed the influence of macroclimatic variables on termite species distribution and functional groups. We found 22 taxa of two families, of which the most frequent species were Termitidae (96.51%). Within this family, Apicotermitinae had the highest frequency of occurrence (37.12%), followed by Termitinae (30.57%), Syntermitinae (27.95%), and Nasutitermitinae (0.8 %). The other family, Rhinotermitidae, had the lowest frequency (3.5%), being represented only by Heterotermes sulcatus Mathews. We classified Neocapritermes opacus Hagen (29.26%), Apicotermitinae sp.2 (24.89%), Cornitermes cumulans Kollar (13.10%), and Apicotermitinae sp.1 (6.99%) as common taxa. The remaining 18 species were classified as rare. The most common functional group was humus-feeders (37%), followed by wood-feeders (34%), grass-litter feeders (25%), and intermediate feeders (4%). Climate influenced the distribution of common species, humus-feeders and grass-litter feeders. Regarding the pest status of termites in sugar cane plantations, we suggest that the exasperated use of pesticide in the last decades has reduced the abundance of species considered pests (e.g. Heterotermes) and reinforce the importance of ecological approaches for determining the best pest control methods. Comunidades de Cupins em Cultivos de Cana-de-Açúcar no Estado de São Paulo: Uma Abordagem Ecológica Resumo. Os cupins são importantes componentes da fauna de solo, atuando na decomposição da matéria orgânica e ciclagem de nutrientes. Porém, em cultivos de cana-de-açúcar, podem provocar perdas econômicas significativas. A correta identificação das espécies de cupins é um ponto crítico para o controle daquelas que adquiriram e/ou que podem atingir o status de praga. Este trabalho objetivou identificar a riqueza, a abundância e os grupos funcionais destes insetos em canaviais de 53 municípios do estado de São Paulo. Paralelamente, avaliou se as variáveis macroclimáticas influenciam a distribuição das comunidades de cupins e dos grupos funcionais. A riqueza obtida foi de 22 táxons. Da família Termitidae (96,51%), a maior frequência de ocorrência foi da subfamília Apicotermitinae (37,12%), seguindo-se Termitinae (30,57%), Syntermitinae (27,95%) e Nasutitermitinae (0,8%). A família Rhinotermitidae (3,5%) esteve representada apenas por Heterotermes sulcatus Mathews. Quatro táxons foram considerados comuns em canaviais, Neocapritermes opacus Hagen (29,26%), Apicotermitinae sp.2 (24,89%), Cornitermes cumulans Kollar (13,10%) e Apicotermitinae sp.1 (6,99%) e os 18 restantes foram classificados como raros. O grupo funcional mais frequente foi o dos humívoros (37%), seguido por xilófagos (34%), comedores de serrapilheira (25%) e intermediários (4%). O clima influenciou a distribuição das espécies comuns, bem como dos grupos funcionais dos humívoros e dos comedores de serrapilheira. Sugere-se que o uso intensivo de pesticidas nas últimas décadas reduziu a abundância de espécies até então consideradas praga em cana-de-açúcar (ex. Heterotermes), o que reforça a importância dos estudos ecológicos para a definição de métodos de controle mais adequados.